ANALISIS PENGARUH INKLUSI KEUANGAN TERHADAP KEMISKINAN DI INDONESIA - Prakarsa, Daffa Yudha; Bintoro, Nugroho Suryo (Contemporary Studies in Economic, Finance and Banking, 2023)
Poverty still a major problem in developing countries, including Indonesia. Various efforts have been made to alleviate poverty, one of which is through financial inclusion. This research attempts to identify and analyze the effect of financial inclusion on poverty in Indonesia. This research uses panel data from 34 provinces in Indonesia during 2018-2021. The regression model used is panel data regression. Testing the hypothesis with t test and F test. The results showed that the financial inclusion dimension of accessibility has a negative and significant effect, the financial inclusion dimension of availability has a negative and insignificant effect, and GRDP per capita has a negative effect although not significant on poverty in 34 provinces in Indonesia. Meanwhile, the financial inclusion dimension of use has a positive and significant effect on poverty in 34 provinces in Indonesia. This indicates that the use of financial services can actually increase poverty in 34 provinces in Indonesia. Financial inclusion dimensions of the use of financial services are still minimal for the poor. So that increasing the use of financial services must pay attention to the poor. The government also needs to pay attention to increasing financial inclusion which is more evenly distributed between provinces.